Characterization of Selenium Nanostructures Synthesized by Aerobic Microbial Route - Goyal, Kashika (My University, 2010)
Selenium is a non-metallic chemical element, and exhibits many properties like relatively high photoconductivity, high piezoelectric, thermoelectric, and non linear optical responses especially in nanocrystalline form. Selenium nanostructures have been synthesized by aerobic microbial manufacture process. The Se nanostructures produced by the microbe are amorphous, nearly spherical and held together in clusters by a protein coating. The thermal and structural properties of these nanostructures have been studied. Thermal properties of these nanostructures have been studied by DTA and TGA thermograms. Removal of the protein coating by washing with acetone results in growth of crystalline nanostructures. Another method for inducing crystallization is temperature. Heating to ~100 C results in the formation of crystalline phase. The nanostructure morphology stays the same. The crystalline phase formed in both the routes is hexagonal and the unit cell dimensions are: a = 0.4462 nm, c = 0.4980 nm. These results imply that the Se nanostructures produced by the microbe are actually clusters of Se atoms held together in a metastable state by a protein coat. This metastable state can be destroyed either by removing the protein coating or by heat treatment which retains the protein coat and hence the shape, but provides enough energy to the atoms within the cluster to crystallize.
M.Sc. (Physics)
Keywords: Selenium; Biosynthesis of Nanostructures; Nanoparticles; Aerobic Bacteria